IBSP, a potential recurrence biomarker, promotes the progression of colorectal cancer via Fyn/β‐catenin signaling pathway. (13th May 2021) - Chen, Yan; Qin, Ying; Dai, Mengmeng; Liu, Liping; Ni, Yong; Sun, Qinsheng; Li, Lulu; Zhou, Yaoyao; Qiu, Cheng; Jiang, Yuyang
Abstract: Colorectal cancer (CRC) is a frequently occurring digestive system cancer and postoperative tumor metastasis and recurrence are the main reasons for the failure of CRC treatment. The aim of this study was to identifying and validating key genes associated with metastatic recurrence of CRC. RNA expression of three datasets (GSE17538, GSE32323, and GSE29623 ) was used for biomarker discovery. We identified integrin‐binding sialoprotein (IBSP) as a candidate biomarker which was validated in three clinical cohorts (GSE41258, GSE21510, and GSE39582 ) and our clinical specimens. The results suggested that IBSP expression significantly increased at mRNA and protein levels among CRC cases, which was associated with metastatic recurrence, metastasis, high risk of recurrence, and poor survival in CRC. Consistent results were obtained in CRC cells. The relative level of serum IBSP evidently increased among CRC patients relative to normal controls, and downregulated after operation. As suggested by gene set enrichment analysis (GSEA), the IBSP level was associated with cell‐matrix adhesion in CRC. Functional experiments in vitro showed that IBSP promoted the growth and aggressiveness of CRC, and the potential mechanism by which IBSP promoted carcinogenesis of CRC was the abnormal activation of Fyn/β‐catenin signaling pathway. To sum up, findings in the present work indicate that IBSP can serve as the candidate biomarker for the diagnosis, treatment, and prognosis of CRC. Abstract : In this study, we identified and validated IBSP as a key gene associated with metastatic recurrence of CRC which might serve as the candidate biomarker for the diagnosis, treatment, and prognosis of CRC. Our results suggested that IBSP expression significantly increased at mRNA and protein levels among CRC cases, which was associated with metastatic recurrence, metastasis, high risk of recurrence, and poor survival in CRC. Functional experiments in vitro showed that IBSP promoted the growth and aggressiveness of CRC, and the potential mechanism by which IBSP promoted carcinogenesis of CRC was the abnormal activation of Fyn/β‐catenin signaling pathway.